Comparative Morphology of Sperm in The Rat (Rattus novergicus) Exposed to Cadmium(Cd) and Mercury (Hg) with Green Coconut Water (Cocos nucifera L.) as Antidontum - Mustika, Ika; Tyastirin, Esti; Rachmawati, Yuanita (International Conference on Sustainable Health Promotion, 2018)
Environmental conditions more polluted by heavy metal Cd and Hg resulted in various effects of toxicity to humans. One of them is an abnormality sperm morphology which can affect the occurrence of infertility. Green coconut water is plants that contain a variety of vitamins, minerals, amino acids and tannins that can be used to remove the toxins in the body. This research aims to know the difference count of the normal sperm and abnormal sperm morphology in rats exposed Cd and Hg with the giving of the Green coconut water. Research carried out experimentally using a Rattus novergicus which exposure two µ g/mL Cd and Hg. Rats were divided into six groups, each of which are exposed to metals Cd, Hg, Cd with green coconut water, Cd with green coconut water, and green coconut water as a control. The research results obtained a p-value for normal sperm count of 0.014, whereas in abnormal sperm count p-value 0.008 so it can be concluded there is a significant difference in the number of normal or abnormal sperm morphology of rat exposed Cd and Hg with the giving of the Green coconut water. The giving of green coconut water helps reduce effects sperm damage due to exposure Cd and Hg.